2004
DOI: 10.1002/cphc.200400156
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Investigation of the Selective Oxidation of Methane to Methanol on Nanostructured Fe‐ZSM‐5 by the ONIOM Method

Abstract: Nanostructured Fe‐ZSM‐5: Structures and reactivities of an Fe‐exchanged ZSM‐5 zeolite (see picture, the blue and red spheres represent Fe and O atoms, respectively) for decomposition of nitrous oxide and oxidation of methane to methanol were investigated using density functional theory calculations and a two‐layered ONIOM (our own n‐layer integrated molecular orbital and molecular mechanics) scheme that explicitly takes into account the extended zeolitic framework.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
61
1
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 57 publications
(75 citation statements)
references
References 51 publications
11
61
1
2
Order By: Relevance
“…Hence, small quantum cluster calculations which basically neglect these interactions can give erroneous results. However, hybrid methods such as QM/MM and ONIOM can reasonably describe these interactions [12][13][14][15] with only a small increase in computational demand. Therefore, we used the ONIOM method to investigate ethylene dimerization inside faujasite zeolite.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, small quantum cluster calculations which basically neglect these interactions can give erroneous results. However, hybrid methods such as QM/MM and ONIOM can reasonably describe these interactions [12][13][14][15] with only a small increase in computational demand. Therefore, we used the ONIOM method to investigate ethylene dimerization inside faujasite zeolite.…”
Section: Resultsmentioning
confidence: 99%
“…The recent development of hybrid methods, such as embedded cluster or combined quantum mechanics/molecular mechanics (QM/MM) methods, as well as the more general ONIOM (our own n-layered integrated molecular orbital and molecular mechanics) method [11] has brought obtaining accurate results on larger systems within reach. Recent theoretical studies [12][13][14][15] have shown that the ONIOM scheme can be efficiently used for characterizing the reactivity of active sites inside zeolites.…”
Section: Introductionmentioning
confidence: 99%
“…Among the numerous competing active sites in Fe/ZSM-5 zeolite, the mono-iron species has been the most extensively studied [34][35][36][37][38][39][40][41][42]. It is probably due to two reasons.…”
Section: The Mono-iron Speciesmentioning
confidence: 98%
“…The cluster model is similar to that used in our previous study on isolated metal oxide on zeolite. [12] The [VO 2 ] ionic group lies between the two bridging oxygen atoms of the zeolite framework forming a tetrahedral arrangement at the vanadium atom, which is the most stable configuration. With the M06-L functional and the 6-31G(d,p) basis set, the optimized VÀO bond lengths are 1.59, 1.59, 1.98, and 1.98 for VÀO1, VÀO2, VÀOa, and VÀOb, respectively.…”
Section: Propane Adsorption Over the Catalystmentioning
confidence: 99%